Pediatrician Attitudes toward Digital Voice Assistant Technology Use in Clinical Practice - Wilder, Jayme L.; Nadar, Devin; Gujral, Nitin; Ortiz, Benjamin; Stevens, Robert; Holder-Niles, Faye; Lee, John; Gaffin, Jonathan M. (Applied Clinical Informatics, 2019)
Objective Digital voice assistant technology provides unique opportunities to enhance clinical practice. We aimed to understand factors influencing pediatric providers' current and potential use of this technology in clinical practice.Methods We surveyed pediatric providers regarding current use and interest in voice technology in the workplace. Regression analyses evaluated provider characteristics associated with voice technology use. Among respondents not interested in voice technology, we elicited individual concerns.Results Among 114 respondents, 19 (16.7%) indicated current use of voice technology in clinical practice, and 51 (44.7%) indicated use of voice technology for nonclinical purposes. Fifty-four (47.4%) reported willingness to try digital voice assistant technology in the clinical setting. Providers who had longer clinic visits (odds ratio [OR], 3.11, 95% confidence interval [CI], 1.04, 9.33, p = 0.04), fewer patient encounters per day (p = 0.02), and worked in hospital-based practices (OR, 2.95, 95% CI, 1.08, 8.07, p = 0.03) were more likely to currently use voice technology in the office. Younger providers (p = 0.02) and those confident in the accuracy of voice technology (OR, 3.05, 95% CI, 1.38, 6.74, p = 0.005) were more willing to trial digital voice assistants in the clinical setting. Among respondents unwilling or unsure about trying voice assistant technology, the most common reasons elicited were concerns related to its accuracy (35%), efficiency (33%), and privacy (28%).Conclusion This national survey evaluating use and attitudes toward digital voice assistant technology by pediatric providers found that while only one-eighth of pediatric providers currently use digital voice assistant technology in the clinical setting, almost half are interested in trying it in the future. Younger provider age and confidence in the accuracy of voice technology are associated with provider interest in using voice technology in the clinical setting. Future development of voice technology for clinical use will need to consider accuracy of information, efficiency of use, and patient privacy for successful integration into the workplace.
Keywords: mobile health; human–computer interaction; speech recognition software; workflow; pediatrics